Arming the British Home Guard, 1940-1944 - Clarke, D M (Security Studies Institute Department of Management and SecurityT AND SECURITY, 2011)
The Second World War saw British society mobilised to an unprecedented extent to meet the threat of Total War. ‘Total Defence’ was manifest in organisations such as the ARP and Home Guard. What sets the Home Guard apart was its combatant role. This thesis examines the arms provided for the Home Guard, and concludes that its combat power has been seriously underestimated. It benefitted from huge quantities of high quality smallarms purchased from the United States, which were not issued to the Regular Army, because they chambered American ammunition. What is extraordinary is that these weapons are always characterised as ancient relics, yet the oldest of them was years younger, in real and design terms, than the British Army equivalent. In 1940 Britain lacked the capacity to manufacture arms in the quantities needed to repair the losses of Dunkirk and meet the needs of the expanding armed forces. The remedy was unorthodox weaponry such as the ‘Sticky Bomb’ and the ‘Blacker Bombard’. These are always associated with the Home Guard, yet saw active service against the Africa Corps. These unconventional weapons were more capable than many modern authors suggest, but they suffer from an impenetrable ‘orthodox view’ that characterises Home Guard weapons as ancient, whimsical and inefficient. This has its origins in the Local Defence Volunteers’ disappointment when the Government failed to meet its promise to arm every volunteer; their dismay at receiving foreign equipment; the way in which the media portrayed the Home Guard; and the fact that the great threats the Home Guard existed to combat – invasion and subversion – appeared to be illusory, making the Home Guard itself seem quixotic. This study strips away that conventional narrative, and exposes a Home Guard that was well equipped for its tasks – frequently better equipped than other components of Home Defence.